Prospective analysis of the implications of using autonomous aerial systems in USAF Air Defense Interception Missions. From 2019 to 2035 - Correa Rubio, Juan Camilo (Journal of the Spanish Institute for Strategic Studies, 2021)
Robotization of the battlefield is no longer a science fiction concept. Successful tests with autonomous weapon systems, give way to a new Revolution in Military Affairs, which is located in the incipient era of robotics and nano-technology. Through the construction and analysis of scenarios technique, four scenarios and their implications are studied, in air defense interception missions in US domestic airspace. Set as the horizon fiscal year 2035, the key concept within the autonomous UAS for this study is that of the loyal wingman.